Design and Development of an ESP8266-Based Digital Thermometer Using a DHT22 Sensor with OLED Display Output - Janeta Wahyu Hidayah; Hari Purwadi; Ansar Rizal (Lembaga Pengembangan Kinerja Dosen, 2026)
The advancement of microcontroller technology enables the development of accurate and practical temperature measurement devices. This study aims to design and build a digital thermometer based on ESP8266 using a DHT22 sensor to measure air temperature and humidity in real time, with the measurement results displayed on an OLED screen. The research methodology includes circuit design, microcontroller programming, sensor calibration, and system testing by comparing the measurement results with reference instruments. The test results indicate that the system operates stably and responsively. The average temperature measurement deviation compared to the reference thermometer is 6.26 °C , while the average humidity measurement deviation compared to the digital hygrometer is 4.56 %RH . These results indicate that the DHT22 sensor provides acceptable accuracy and remains within tolerable limits for environmental monitoring applications